A look at the high energy aspects of the supernova remnant G309.8+00.0 with eROSITA and Fermi -LAT - Michailidis, M.; Pühlhofer, G.; Santangelo, A.; Sasaki, M.; Becker, W. (Astronomy and astrophysics (Berlin), 2024)
Supernova remnant (SNR) detection along the Galactic plane poses a number of challenges. A diffuse X-ray emission component emanating from unidentified sources on the Galactic plane further complicates such a detection in X-rays. Due to the presence of dense dust clouds along the Galactic plane, X-ray photons are also subject to high absorption. Similarly, diffuse signals from the Galactic plane cause γ -ray contamination from the signal of individual objects. The SNR G309.8+00.0 lies exactly on the Galactic plane, with its center coinciding with galactic latitude (b) = 0°. In this paper we report the first detection of the SNR G309.8+00.0 in X-rays and γ rays, using stacked data from the first four consecutive extended ROentgen Survey Imaging Telescope Array (eROSITA) – on board the Russian-German Spektrum Roentgen Gamma (SRG) – all-sky surveys (eRASS:4) and ∼15.5 yr of Pass 8 data recorded from Fermi -LAT, respectively. The SNR appears to have an elliptical shape of 0 ọ 43 × 0 ọ 32 in size in both radio synchrotron and X-ray data. The SNR’s emission exhibits a shell-like morphology and good spatial correlation in both energy bands. The X-ray emission was solely detected in the 1–2 keV energy band (subject to strong absorption at soft X-rays) and the spectral analysis results of eRASS:4 data present a purely thermal SNR with a high absorption column density 3.1 +0.7 -0.5 ⋅ 10 22 cm -2 and a temperature of 0.34 ± 0.1 keV. Although the thermal plasma appears to be in equilibrium, the limited statistics do not allow us to exclude nonequilibrium models. The X-ray spectral analysis of the remnant resulted in the detection of relatively (given the limited statistics) prominent Mg triplet lines at 1.33–1.47 keV and silicon (Si XIII) at 1.74–1.9 keV energies. In combination with optical extinction data, the absorption column density values derived from the remnant’s spectral analysis support a remnant’s distance greater than 6 kpc, rather than a 3.12 kpc distance as reported in the literature, and yield an age of 1 − 3.5 ⋅ 10 5 yr. Employing ∼15.5 yr of Fermi -LAT γ -ray data at and around the remnant’s vicinity, we confirm the detection of the to-date unidentified 4FGL J1349.5−6206c source that can either be modeled as a single source or a conglomerate of multiple distinct source components. In the latter case, the detailed inspection of the Fermi -LAT γ -ray data in the direction of the remnant allowed us to decompose the 4FGL J1349.5−6206c source into four point-like components, among which one is spatially coincident with the SNR G309.8+00.0 shell. We detected the component that spatially coincides with the SNR with a significance of 5.8 σ above 1 GeV with Fermi -LAT and thus argue that the SNR G309.8+00.0 likely represents at least a significant portion (if not all) of the emission from the 4FGL J1349.5−6206c γ -ray source, detected with 9.8 σ significance > 1 GeV with Fermi -LAT.